Decreased serum 1,5-anhydroglucitol in nondiabetic subjects with a family history of NIDDM - Tsukui, Satoshi; Fukumura, Yukihito; Kobayashi, Isao (Diabetes Caer, 1996)
Decreased serum 1,5-anhydroglucitol in nondiabetic subjects with a family history of NIDDM. S Tsukui , Y Fukumura and I Kobayashi Department of Laboratory Medicine, Gunma University School of Medicine, Japan. pxk04327@niftyserve.or.jp Abstract OBJECTIVE: To investigate the effect of a family history of NIDDM on HbAlc and serum 1,5-anhydroglucitol (AG) in nondiabetic subjects. RESEARCH DESIGN AND METHODS: A 75-g oral glucose tolerance test was performed; 258 subjects with normal glucose tolerance and 106 subjects with impaired glucose tolerance (IGT) were selected HbAlc and serum AG were compared between subjects with and without a family history of NIDDM. The relationships between age, BMI, HbAlc, serum AG, fasting and 2-h plasma glucose, and urinary glucose were also examined using principal component analysis with a varimax rotation. RESULTS: In the normal group, only serum AG was lower in subjects with a positive family history than in those with no family history. On the other hand, in the IGT group, subjects with a positive family history were younger and had a higher 2-h plasma glucose, a higher urinary glucose, and a lower serum AG than those with no family history, whereas there was no difference in HbAlc. Principal component analysis identified three factors. The first factor, a linear combination of HbAlc and fasting plasma glucose, was labeled an average glycemic factor. The second factor, which included serum AG, 2-h plasma glucose, and urinary glucose, was labeled an oscillatory glycemic factor. The third factor, which contrasted age against BMI, was labeled an environmental factor. CONCLUSIONS: Serum AG is related to glycosuria even among nondiabetic subjects, and its concentrations are decreased in those with a family history of NIDDM. Our results suggest that serum AG rather than HbAlc reflects early metabolic abnormalities in these subjects.